Integralidade do cuidado para indivíduos com doenças genéticas raras que afetam o desenvolvimento esquelético: fatores associados ao acesso ao serviço de saúde bucal - Suélen Alves Teixeira Debossan (2020)
Rare genetic diseases are considered pathological events of low-occurrence genetic origin and with wide diversity of signs and symptoms. Generally, individuals affected with rare diseases present muscle, skeletal and central nervous system alterations. Many orofacial manifestations are common in this part of the population, that in the vast majority of time it has difficulty accessing adequate dental treatment. The concept of comprehensive care is widely discussed both in health practices, then discussions related to the understanding of the human being, of his integral and non-partial condition. This study aimed to identify factors associated with access to oral health service for individuals with rare genetic disease and without rare genetic disease. A cross-sectional study was conducted, matched by sex and age, with 140 individuals [70 with rare genetic disease - Mucopolysaccharidosis (n=29) / Osteogenesis Imperfect (n=41) - and 70 without rare genetic disease] and parents/guardians. The sample was selected in two reference hospitals for patients with rare diseases in Minas Gerais, southeastern Brazil. Parents/guardians answered a questionnaire about individual aspects and medical and dental history of the child. Participants with rare disease and without rare disease were examined for dental caries, malocclusion, dental anomalies and oral hygiene. The theoretical model of the Directed Acyclic Graphs (DAG) was used to identify possible confounding variables in the association between rare diseases and access to oral health service. The study was approved by the Research Ethics Committee of Federal University of Minas Gerais. Unadjusted and adjusted conditional logistic regression analyzes were performed (p<0.05). The age group of the individuals examined was three to 27 years, with a mean age of 10.3 years (±6.5). The chance of the individual without rare genetic disease belonging to the group with access to oral health service was 5.32 times higher (IC95%: 2.35-12.01). Individuals without episodes of upper airway infections (less than six months) were 3.16 times more likely to be in the group with access to oral health service (IC95%: 1.45-6.90). It was concluded that individuals without rare disease and without history of upper airway infections (< 6 months) were more likely to belong to the group of individuals with access to oral health services.